Peripheral arterial disease affects kinematics during walking - Celis, Rolando; Pipinos, Iraklis I.; Scott-Pandorf, Melissa M.; Myers, Sara A.; Stergiou, Nicholas; Johanning, Jason M. (Journal of vascular surgery, 2009)
Claudication is the most common manifestation of peripheral arterial disease (PAD) producing significant ambulatory compromise. The purpose of this study was to use advanced biomechanical analysis to characterize the kinematic ambulatory pattern of claudicating patients. We hypothesized that compared with control subjects, claudicating patients have altered kinematic gait patterns that can be fully characterized utilizing advanced biomechanical analysis. The study examined fourteen PAD patients (age: 58 ± 3.4 years; weight: 80.99 ± 15.64 kg) with clinically diagnosed femoro-popliteal occlusive disease (Ankle Brachial Index (ABI): 0.56 ± 0.03, range 0.45 to 0.65) and five healthy controls (age: 53 ± 3.4 years; weight: 87.38 ± 12.75 kg; ABI ≥ 1). Kinematic parameters (hip, knee, and ankle joint angles in the sagittal plane) were evaluated during gait in patients before and after the onset of claudication pain and compared with healthy controls. Joint angles were calculated during stance time. Dependent variables were assessed (maximum and minimum flexion and extension angles and ranges of motion) and mean ensemble curves were generated. Time to occurrence of the discrete variables was also identified. Significantly greater ankle plantar flexion in early stance and ankle range of motion during stance was observed in PAD patients ( P < .05). Time to maximum ankle plantar flexion was shorter and time to maximum ankle dorsiflexion was longer in PAD patients ( P < .05). These differences were noted when comparing PAD patients prior to and after the onset of claudication with healthy controls. The analysis of the kinematic parameters of the knee and the hip joints revealed no significant differences between PAD patients and controls. PAD patients with claudication demonstrate significant gait alterations in the ankle joint that are present prior to the onset of claudication pain. In contrast, the joint motion of the hip and knee did not differ in PAD patients when compared with controls. Further research is needed to verify our findings and assess the impact of more proximal disease in PAD patients as well as the effect of revascularization on joint kinematics.